O belo, o forte e o saudável : eugenia e representações nazistas nas obras e narrativas de Leni Riefenstahl (1945-2002) - Ana Luiza Ianeles dos Santos (2021)
Third Reich filmmaker Leni Riefenstahl (1902 – 2003), tried and considered only as “fellow traveler” by the post-war Denazification Courts, never managed to leave behind the “Nazi filmmaker” stigma that was legitimately imposed on her. On the contrary, seeking to justify herself and give new meaning to her image, she denied until her death any political or propagandistic aspect of her works, claiming, among other arguments, that she only loved what is “beautiful, strong and healthy.” However, based on Reinhart Koselleck’s understanding that polysemy is a fundamental part of a concept, this thesis seeks to analyze the historicity of these three concepts from their mobilization in eugenic movements and Nazi ideology. In this way, we intend not only to identify the Nazi representations and the discursive aspect of eugenics in the filmmaker’s works and narratives; but also to understand what is established as “positive eugenics” and how we still live with their echoes in this long post-war period.